Zachary T. Smith and Wayne Calloway - (:unkn) unknown (Z. Smith Reynolds Library, 1980)
February 1980?
Zachary T. Smith talking with Wayne Calloway.
Keywords: Forsyth County (N.C.) -- History -- Sources; Forsyth County (N.C.) -- History -- Pictorial works; Digital Forsyth; Smith, Zachary T.; Calloway, Wayne